A Mapping Halal Tourism Management Research: Text Mining using NVivo - Silma Lafifa Sunarya; Sabiq Al Qital (Jurnal Pariwisata Nusantara (JUWITA), 2022)
Purpose: This study aims to identify and map the research related to the current development of Halal Tourism Management research. Method: The method used is qualitative by using literature studies from various published articles indexed by Scopus for the period 1997-2022 which were collected on May 11, 2022. The data were processed with Microsoft Excel 16 and analyzed using Nvivo 12 Plus software to perform coding and classification automatically. Results: The results show that there is a fluctuating improvement in halal tourism management during the 25-year observation period. There are 3 interesting things in the discussion of halal tourism management. First, halal is a basic reference in the development of tourism objects and halal tourism management. Second, tourists as a challenge in the halal tourism management system. Third, is the development of sustainable halal tourism industry. Contribution: This research formulates a strategy for the development of halal tourism management. This strategy focuses on halal tourism objects, marketing, and institutions. This research can be used as an additional study related to the Halal Tourism sector and has the potential to be developed.